Organic tandem solar cells with 18.6% efficiency. (1st March 2020) - Salim, Muath Bani; Nekovei, Reza; Jeyakumar, R.
Highlights: Numerical Simulation for 676 Tandem organic photovoltaic (TOPV) devices. Find new TOPV devices that can give power conversion efficiency (PCE) more than 15%. PCE of 18.6% is reported for PBDTS-TDZ: ITIC in the Tandem front cells and PTB7-Th: O6T-4F:PC71BM in the Tandem back cell. Effect of the active layers thickness and optimization for the new TOPV active layer thickness. Abstract: Tandem organic photovoltaic (TOPV) cell is one of the technologies to harvest more solar power by staking two or more OPV devices on top of each other. Recently, the highest power conversion efficiency (PCE) ever achieved was 17.3%. Herein, this paper simulates the response of 676‬ different TOPV devices that consists front and back OPV cells. For this purpose, this paper uses the best 26 single-cell OPV devices to form the TOPV front and back cells combinations. The results show that there are some new TOPVs that can exceed 17.3% efficiency limit for TOPV. Also, in this work thickness optimization was performed for these new TOPV devices with an objective of efficiency maximization. As a result, using PBDTS-TDZ: ITIC in the front cells and PTB7-Th: O6T-4F:PC71BM in the back cell gives 18.6% efficiency. Likewise, the TOPV of PBDB-T-2F:TfIF-4FIC in the front cell with PTB7-Th:O6T-4F:PC71BM in the back cell gives 18.06% efficiency.